Modelling Airway Management using System Reliability Assessment Tools - Almghairbi, Dalal; Chetan Reddy; Iain Moppett (AlQalam Journal of Medical and Applied Sciences, 2024)
Airway management can be considered as a complex engineering process which includes a series of sequential or simultaneous actions (e.g., tasks or decisions) using different resources i.e., time, people, equipment and medications. We explored the decision-making and actions during the process of routine airway management. To elicit an understanding of cognitive strategies applied and influences on strategy selection using the Critical Decision Method. The task steps involved in action and decision making during the induction of routine airway process in both routine and complicated cases were identified using hierarchical task analysis. The systematic human error reduction and prediction approach was then used to examine the task steps at the lowest level of hierarchical task analysis in more detail. There were differences in airway practice and preparation between participants. The decisions were primarily made by the lead consultant anaesthetist, with the trainees and Operating Department Practitioners (anaesthetic nurse) supporting these decisions. Much of the team communication used code language, which appeared to be well understood by the team members and did not obviously impede performance in the context of routine airway management. Most of the experienced lead consultant anaesthetists rely on their past experience of "work-as-done" during the airway process. The results from this study illustrated that human factors and non-technical skills are important for airway management and for ensuring safe, high-quality intraoperative care. Further research is needed to determine how these skills work in conjunction and how they impact anaesthetic performance. يمكن اعتبار إدارة مجرى الهواء عملية هندسية معقدة تتضمن سلسلة من الإجراءات المتسلسلة أو المتزامنة (مثل المهام أو القرارات) باستخدام موارد مختلفة، أي الوقت والأشخاص والمعدات والأدوية. استكشفنا عملية اتخاذ القرار والإجراءات أثناء عملية إدارة مجرى الهواء الروتينية. لاستنباط فهم للإستراتيجيات المعرفية المطبقة وتأثيراتها على اختيار الإستراتيجية باستخدام طريقة القرار الحاسم. تم تحديد خطوات المهمة المشاركة في العمل واتخاذ القرار أثناء إدخال عملية مجرى الهواء الروتينية في كل من الحالات الروتينية والمعقدة باستخدام تحليل المهام الهرمي. ثم تم استخدام نهج تقليل الأخطاء البشرية والتنبؤ بها بشكل منهجي لفحص خطوات المهمة على أدنى مستوى من تحليل المهام الهرمي بمزيد من التفصيل. كانت هناك اختلافات في ممارسة مجرى الهواء والتحضير بين المشاركين. تم اتخاذ القرارات في المقام الأول من قبل استشاري التخدير الرئيسي، مع دعم المتدربين وممارسي قسم العمليات (ممرضة التخدير) لهذه القرارات. وقد استخدم الفريق في كثير من اتصالاته لغة مشفرة، والتي بدا أن أعضاء الفريق يفهمونها جيدًا ولم تعيق الأداء بشكل واضح في سياق إدارة مجرى الهواء الروتيني. ويعتمد معظم استشاريي التخدير ذوي الخبرة على خبرتهم السابقة في "العمل كما تم" أثناء عملية مجرى الهواء. وقد أوضحت نتائج هذه الدراسة أن العوامل البشرية والمهارات غير الفنية مهمة لإدارة مجرى الهواء وضمان رعاية آمنة وعالية الجودة أثناء الجراحة. وهناك حاجة إلى مزيد من البحث لتحديد كيفية عمل هذه المهارات معًا وكيف تؤثر على أداء التخدير